Peran Sasi Dalam Pelestarian Fauna Sebuah Perspektif Kearifan Lokal - Astini Jakomina; Edoardus E Maturbongs (Department of State Administration - Musamus University, 2021)
Sasi is one form/way to maintain and preserve the existing natural resources in order not to happen extinction through customs or traditions that have been carried out since long ago. Research aims to know local wisdom in the preservation of fauna in the village Torai District Sota Merauke District. The research methods used are qualitative descriptive with data analysis techniques using the Miles and Huberman models i.e. data reduction, data presentation, and withdrawal of conclusions or verification. The total number of informant in this research was 6 people. Results of the research on local wisdom in the preservation of Fauna in village Torai District Sota Kabupaten Merauke has not been executed properly in accordance with the prohibition of actual retainer and sanctions given for the offenders also not in accordance with the used in the past due to economic factors that influence so that the Sasi in village g Torai has begun to disappear slowly or has begun to be done rarely when this tradition has been done since long ago.